2019
DOI: 10.1039/c9ra08761c
|View full text |Cite
|
Sign up to set email alerts
|

Selective recognition of human telomeric G-quadruplex with designed peptide via hydrogen bonding followed by base stacking interactions

Abstract: A new synthetic peptide is presented. A Glu residue binds through H-bonding to a guanine-base and a Trp residue intercalates with K+ resulting in stabilization of a human telomeric G-quadruplex with high selectivity over a complementary c-rich strand and double-stranded DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…These results are consistent with our recently published results where we have shown that the Human telomere G4 was not binding with QW10 in the presence of Na + . 31 In contrast, c-Myc promoter G4 in the presence of K + exhibited a strong positive peak around 268 nm and negative peak at 239 nm indicating the same characteristics of parallel G-quadruplex 27 ( Fig. 2b ).…”
Section: Methodsmentioning
confidence: 92%
“…These results are consistent with our recently published results where we have shown that the Human telomere G4 was not binding with QW10 in the presence of Na + . 31 In contrast, c-Myc promoter G4 in the presence of K + exhibited a strong positive peak around 268 nm and negative peak at 239 nm indicating the same characteristics of parallel G-quadruplex 27 ( Fig. 2b ).…”
Section: Methodsmentioning
confidence: 92%
“…QW10 was chosen to incorporate glutamine amino acid for its capacity as hydrogen bond donor and acceptor with guanine, and tryptophan to provide π-stacking with the quartet in an intercalative mode. [66] No positively charged residues were incorporated to prevent non-specific binding to duplex DNA. Molecular docking studies demonstrated that this peptide is able to effectively intercalate between the G4 tetrads through tryptophan residues and develops hydrogen bonds through glutamine residues.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...mentioning
confidence: 99%
“…Chemical structure of the dendritic peptide synthesized by Biswas et al [65] presence of Na + based buffer), thus implying a structuredependent binding mode. [66] Bloom syndrome (BLM) protein is a helicase able to unwind human telomeric G4. As a matter of fact, BLM possesses a helicase-and-RNase-D C-Terminal domain, named HRDC, able to bind single stranded DNA.…”
Section: Artificially and Naturally Derived Peptides Interacting Spec...mentioning
confidence: 99%
“…Systems capable of controlling DNA and RNA G-quadruplex structures would be useful for the modulation of various cellular events and different G-quadruplex-targeting ligands have been described [ 17 , 18 ], including phthalocyanine [ 19 ], porphyrin [ 20 ], and other derivatives [ 21 , 22 ]. From these, peptides represent a class of highly specific ligands with a greater degree of functionality including binding on-off switching, cellular penetration, and the ability to target organelles [ 23 , 24 , 25 , 26 , 27 ]. Among them, the N-terminal domain of the RNA helicase associated with AU-rich element (RHAU), a member of the human DEAH (Asp-Glu-Ala-His) box family of RNA helicases, which includes a specific motif, named RSM, necessary for G-quadruplex recognition and interaction (aa 54–66) [ 28 ], has recently raised the interest of several authors [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%